The Influence of Organizational Identification, Reputation, Costs, and Infrastructure Factors on New Student Satisfaction at Private Universities - Cindrakasih, Nabilah Amanah; Hartono, Arif (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
This study aims to test and analyze the influence of organizational identification factors, university reputation, tuition fees, and infrastructure on the satisfaction of new students who will later recommend private universities. The research method used is quantitative. This study involved 164 respondents from new students of the 2023 batch of the Islamic University of Indonesia. Data were collected through an online questionnaire using a Google form and analyzed using SPSS and PLS-SEM with SmartPLS software. The results of this study state that organizational identification and tuition fees have a positive and significant effect on student satisfaction. However, the university's reputation and infrastructure do not show a direct positive relationship with student satisfaction. In addition, the results of this study also highlight that student satisfaction has a positive and significant effect on their intention to recommend the university to prospective students. This is very important for university management because it shows that efforts to increase organizational identification and set affordable tuition fees, will later encourage them to recommend the university. This study contributes to the enrichment of higher education marketing literature. This study also recommends marketing managers improve the factors that make students satisfied at the university.